2022
DOI: 10.1039/d2sc02857c
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected molecular diversity of brown carbon formed by Maillard-like reactions in aqueous aerosols

Abstract: We found unexpected molecular diversity of brown carbon formed by Maillard-like reactions in aqueous aerosols, and carbonyl precursors play a more important role in determining the molecular diversity of brown carbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Several PS/cyclohexane solutions of known concentration were prepared and measured to create the calibration curve. The absorption band centered around 260 nm originates from the benzene ring of PS . The intensity of the absorption band increases with increasing polymer concentration (Figure S12a).…”
Section: Methodsmentioning
confidence: 99%
“…Several PS/cyclohexane solutions of known concentration were prepared and measured to create the calibration curve. The absorption band centered around 260 nm originates from the benzene ring of PS . The intensity of the absorption band increases with increasing polymer concentration (Figure S12a).…”
Section: Methodsmentioning
confidence: 99%
“…Figures S1 and S2 in Supporting Information showed time‐dependent absorption spectra of two groups and Figures S3 and S4 in Supporting Information showed absorption index time profiles and kinetics recorded during the reaction of Gly + GX, Ala + GX, Gly/Ala + GX, Gly + MG, Ala + MG, and Gly/Ala + MG. The related experimental results demonstrated organic amines can form BrC with carbonyl compounds in the liquid phase (Tang et al., 2022). Powelson et al.…”
Section: Resultsmentioning
confidence: 99%
“…Figures S1 and S2 in Supporting Information S1 showed time-dependent absorption spectra of two groups and Figures S3 and S4 in Supporting Information S1 showed absorption index time profiles and kinetics recorded during the reaction of Gly + GX, Ala + GX, Gly/Ala + GX, Gly + MG, Ala + MG, and Gly/Ala + MG. The related experimental results demonstrated organic amines can form BrC with carbonyl compounds in the liquid phase (Tang et al, 2022). Powelson et al (2014) reported significantly faster reactions for MG versus GX with bulk phase reactions at pH 4 and the same initial reactants concentrations of 0.05-0.25 M. However, according to the data in Table 1, the reaction rate with GX was higher than that with MG when the bulk reaction was performed at pH 4.9 and different ratios of reactant concentrations.…”
Section: Photosensitized Oxidation Mediated By Brcmentioning
confidence: 92%
See 1 more Smart Citation
“…6,9,11,12 Furthermore, some carbonyl compounds such as glyoxal are precursors for Brown Carbon (BrC) formation. [13][14][15][16][17] Despite the abundance of carbonyl compounds in the atmosphere, for the most part, heterogeneous and multiphase reactions of these compounds on mineral surfaces were considered insignicant due to their volatility. 12 MEK is the second most abundant atmospheric carbonyl compound aer acetone, 11,18 with a typical mixing ratio of 0.03-4 ppb.…”
Section: Introductionmentioning
confidence: 99%